Numeracy Skills Of Junior High School Students In Doing AKM (Minimum Competency Assessment) Type Problems - Fathimatuzzahro, Iffah; Sumartono; Prastiwi, Lusiana (Jurnal Pendidikan Matematika, 2025)
In an effort to improve numeracy skills, the Ministry of Education and Culture has established the National Assessment as a form of education evaluation in Indonesia. The implementation of the National Assessment evaluation is measured through the Minimum Competency Assessment (AKM). The Pythagorean Theorem is one of the chapters that includes geometry and measurement materials, and algebra which requires the ability to analyze and solve problems. Understanding and practice questions using the AKM type of questions are needed so that students can easily interpret mathematical problems that arise in everyday life. The purpose of this study was to describe the numeracy skills of junior high school students in solving AKM type questions on the Pythagorean Theorem material. The subjects of this study were 12 students of Class VIII of SMP Brawijayasakta I Surabaya. This study used a qualitative descriptive method. Data collection techniques in this study were written tests and unstructured interviews. The data analysis technique used by the researcher was triangulation techniques which aimed to ensure the relationship between test results and interview answers. The results of this study indicate that Students in the high numeracy ability category are sufficient to fulfill indicator 1, and can fulfill indicators 2 and 3 well. For students in the low numeracy ability category, it is enough to meet indicator 1, to meet indicator 2 well and not to meet indicator 3. For students in the low numeracy ability category, it is enough to meet indicator 1 and not meet indicators 2 and 3.